Urogenital Fistula Patients Profile at a Tertiary Hospital in Surabaya, Indonesia from 2015 to 2021 - Jamhari, Muhammad Arif Hakim; Soebadi, Mohammad Ayodhia; Renaldo, Johan (Folia Medica Indonesiana, 2022)
Highlights: • Vesicovaginal fistula is the most common urogenital fistula. • The transvaginal approach is preferred in treating urogenital fistula. Abstract: A fistula is an extra-anatomical channel between two or more hollow organs, or between an organ and the body surface. WHO estimated there were two million patients with untreated urogenital fistula, with 130,000 new cases every year. The ideal approach for urogenital fistula depends on surgeon preference and individual clinical characteristics. Accordingly, we aimed to determine the profile of patients with a urogenital fistula at a tertiary hospital of Dr. Soetomo General Academic Hospital in Surabaya, Indonesia, from 2015 to 2021. A retrospective study with a descriptive design was carried out by medical records data retrieval of patients with urogenital fistula. It included age, etiology, anatomical location, surgical management, and recurrence rate. The study population consisted of 55 patients. The majority of the patients were among the 41-50 y.o. age groups (41.17%), while the least were in the <20 years group (1.96%). History of obstructed labor was the most common etiology (70.59%). Fistulas in the study population were also associated with a history of trauma (15.68%) and malignancy (11.76%). The vesicovaginal fistula was the most common type of fistula (88.23%). Other types found include urethrovaginal, ureterovaginal, rectovesical, rectovaginal, and vesicocolon fistulas. The transvaginal approach was preferred in almost all study populations. A total of two cases of vesicovaginal fistula recurred (3.39%). In general, patients with urogenital fistula are prevalent in the 4th decade age group, with the most common etiology being a history of obstructed labor. Transvaginal surgery is the treatment of choice with good results and low recurrence rates.